2020
DOI: 10.1167/iovs.61.4.31
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo CRISPR/Cas9-Mediated Genome Editing Mitigates Photoreceptor Degeneration in a Mouse Model of X-Linked Retinitis Pigmentosa

Abstract: In vivo CRISPR/Cas9-mediated genome editing mitigates photoreceptor degeneration in a mouse model of X-linked retinitis pigmentosa. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Since the first report of AAV-based CRISPR-Cas9 delivery for in vivo genome editing, it has made exciting progress in numerous disease models, including blood disorders 50 , 51 , 52 , metabolic liver diseases 44 , 53 , 54 , 55 , muscular diseases 56 , 57 , 58 , and ocular diseases 59 , 60 . In 2020, in a landmark clinical trial sponsored by Editas Medicines (NCT03872479), AAV became the very first CRISPR-Cas9 delivery vector for direct injection into a patient of Leber congenital amaurosis type 10.…”
Section: Current Vectors For In Vivo Delivery Of Crispr-cas9 Therapeuticsmentioning
confidence: 99%
“…Since the first report of AAV-based CRISPR-Cas9 delivery for in vivo genome editing, it has made exciting progress in numerous disease models, including blood disorders 50 , 51 , 52 , metabolic liver diseases 44 , 53 , 54 , 55 , muscular diseases 56 , 57 , 58 , and ocular diseases 59 , 60 . In 2020, in a landmark clinical trial sponsored by Editas Medicines (NCT03872479), AAV became the very first CRISPR-Cas9 delivery vector for direct injection into a patient of Leber congenital amaurosis type 10.…”
Section: Current Vectors For In Vivo Delivery Of Crispr-cas9 Therapeuticsmentioning
confidence: 99%
“…AAV-mediated gene transfer to treat retinitis pigmentosa has already been approved as the first AAV gene therapy in history, 42 but basic studies on CRISPR-based genome editing for this purpose only started in 2016. Since then, many CRISPR-based approaches, each targeting a different gene ( Nrl 43 44 Mertk , 45 Pde6b , 46 47 Rho , 48 49 and RPGR 50 ), have achieved success in animal models. Specifically, the Nrl gene was depleted via NHEJ or repressed via an approach called CRISPR interference, both instigated by AAV vector delivery of CRISPR components, and the Mertk gene was corrected with a novel method called homology-independent targeted integration.…”
Section: Clinical Applications Of Crispr-based Genome Editingmentioning
confidence: 99%
“…for retinal gene editing and achieved high editing effects in the adult mouse retina [65]. Studies have also demonstrated successful AAV-based CRISPR/Cas9 gene editing in the retina of retinal degeneration mouse model [66,67]. AAV-based delivery of CRISPR/Cas components has also been used to knockdown IGF in the central nervous system [68].…”
Section: Adeno-associated Virusmentioning
confidence: 99%